Interlaced Pd–Ag nanowires rich in grain boundary defects for boosting oxygen reduction electrocatalysis. Issue 9 (26th February 2020) - Liu, Xiao-Jing; Yin, Xing; Sun, Yi-Dan; Yu, Feng-Jiao; Gao, Xiang-Wen; Fu, Li-Jun; Wu, Yu-Ping; Chen, Yu-Hui
Abstract : Pd–Ag interlaced nanowires with grain boundary defect engineering exhibit enhanced activity and superior stability for oxygen reduction reaction in alkaline media. Abstract : Given the high cost and poisoning issues of Pt, developing Pd-based catalysts as substitutes is highly essential. Although substantial progress has been made, the synthesis of Pd-based electrocatalysts with both high activity and stability in the oxygen reduction reaction (ORR) remains a challenge. In this work, we prepared Pd–Ag nanowires with up to micro-sized length and a diameter of ∼17 nm via a facile modified polyol method. The obtained Pd–Ag nanowires (NWs) exhibit interlaced features and are rich in grain boundary defects. Due to the continuous grain boundaries in the one-dimensional (1D) structure and the optimized composition, the synthesized Pd1 Ag1 NWs show half-wave potential of 0.897 V and mass activity of 0.103 A mg −1 in alkaline media toward ORR, higher than those of both state-of-the-art Pt/C and other Pd–Ag counterparts. Significantly, after stability tests over 5000 cycles, Pd1 Ag1 NWs shows a 2 mV positive shift, much better than that of Pt/C, exhibiting striking stability for ORR. This work may provide an avenue to construct advanced catalysts by surface defect engineering.